The Research on the Microscopic Mechanism and Dynamical Characteristics of DC Positive Corona Discharge in Pure O₂ - Jian Sui (IEEE, 2021)
We systematically research the microscopic physical mechanism of positive corona discharge and comprehensively analyse the regular and irregular pulsed oscillations of discharge outputs. Especially, we discover the formation mechanism of irregular pulsed discharge phenomenon for the positive corona and give a profound explanation. According to the physical process of discharge, we propose a new dynamical model which can describe the Trichel pulsed discharge outputs and the characteristics of waveforms. Based on nonlinear dynamics method, we predict and analyse different stages of discharge. In particular, the experimentally observed irregularly pulsed discharge on positive corona is reproduced by the presented theory. Our study reveals that the positive ions as current carriers predominate in the total current and the photons occurring can be treated as the feedback signal in the nonlinear process of discharge system. We find that the photo-ionization is an indispensable role as the source forming electron avalanches for sustaining the positive corona discharge. Moreover, according to quantum mechanics we demonstrate the high frequency photons with energy higher than the ionization energy may photo-ionize oxygen molecules in pure oxygen. We point out that the recombination radiation is competent to photo-ionize neutral molecules producing the seed electrons. Besides, we analyze the characteristics of diversely pulsed outputs and further explain the microscopic mechanism generating the symmetric and asymmetric sharp jagged pulses. Furthermore, we discover the intrinsic physical relations between positive ion and surface electric field, and the significant influences of the attributes of different particles on the discharge behaviors.